Sociabilidade na Web: um estudo sociológico sobre um blog de moda e beleza - Priscila Joyce de Souza Oliveira (2014)
The advent and popularization of information and communication technologies related to web have significantly altered the ways in which individuals establish and maintain relationships today. Taking as an object of study, a fashion and beauty blog, this paper develops a research in two ways, seeking to understand the processes of formation and maintenance of online social networks, examining the nature of the links established between individuals in the interactional context of the blog; analyzing also the ways in which issues concerning gender and consumption are themed the same.